A Unified Volumetric Rate–Energy Relation from Magnetar Radio Bursts to Fast Radio Bursts - Hao-Tian Lan; Shuang-Xi Yi; Fa-Yin Wang (The Astrophysical Journal)
Fast radio bursts (FRBs) are millisecond radio pulses with extremely high bright temperature. Their physical origin is still a mystery. The discovery of FRB 20020428 supports the idea that at least a portion of FRBs is generated by magnetars. However, FRB 20200428 and other radio bursts of SGR 1935+2154 are much less energetic than those of extragalactic FRBs. Thus, whether the progenitors of extragalactic FRBs are magnetars is still controversial. Here, we investigate the volumetric rates of radio bursts from SGR 1935+2154, nonrepeating FRBs, and FRB 20180916B using the uniform samples detected by the Canadian Hydrogen Intensity Mapping Experiment. We find that they share a similar relation between the volumetric rate R and the burst energy E , i.e., R  ∝  E ^− ^γ with γ  = 1.31 ± 0.13 from 10 ^29 to 10 ^42 erg. Our results support the hypothesis that both repeating and nonrepeating FRBs originate from magnetars.